Food security-based strategies for Subak Kedisan organic rice sustainability - Ni Made Classia Sukendar; Widhianthini Widhianthini; Ni Putu Rahayu Sastra Dewi; Trisha Susana Andrea (Institute of Advanced Engineering and Science, 2026)
The Petani Kedisan Mandiri as farmers group in Subak Kedisan has implemented an organic rice farming system and obtained organic certification from Seloliman Organic Certification Agency (LeSOS). However, the group faces challenges in product marketing and limited promotion. This study aims to identify internal and external factors influencing organic rice marketing, formulate alternative marketing strategies, and determine priority strategies for the group. The research applied strengths, weaknesses, opportunities, and threats (SWOT) and quantitative strategic planning matrix (QSPM) analyses. The results identified six internal strengths, with high-quality organic rice as the main strength, and eight weaknesses, with reliance on word-of-mouth marketing as the primary limitation. Six external opportunities were found, particularly the increasing market demand for organic rice, while five major threats were identified, including market segmentation limited to upper-middle-class consumers. Based on the analysis, twelve alternative strategies and one priority strategy were formulated. The main strategy is to enhance digital promotion capacity through training in social media and e-commerce utilization. Recommendations include improving digital literacy, strengthening collaboration with external stakeholders, developing digital infrastructure, leveraging healthy consumption trends, and implementing regular monitoring and evaluation.